Myocardial Fibrosis in Pediatric Heart Disease - Usama Asghar; Samra Choudhry; Mahwish Jabeen; Khadija Mubashir; Ayrass Zia; Mehwish Sadique; Muhammad Jawad Wakil; Laiba Munawar (Cardiology in Review, 2026)
Myocardial fibrosis is increasingly recognized as a central determinant of adverse cardiac remodeling and long-term cardiovascular outcomes in children with congenital and acquired heart disease. Once considered an irreversible consequence of chronic myocardial injury, fibrosis is now understood to represent a dynamic biological process driven by persistent inflammation, neurohormonal activation, oxidative stress, and fibroblast-to-myofibroblast transformation. In pediatric populations, myocardial fibrosis develops across a wide spectrum of diseases including congenital heart disease, cardiomyopathies, myocarditis, pulmonary hypertension, and cancer therapy–related cardiotoxicity. Progressive accumulation of extracellular matrix disrupts myocardial architecture, impairs ventricular compliance, promotes electrical heterogeneity, and predisposes patients to ventricular dysfunction, arrhythmias, heart failure, and sudden cardiac death. Recent advances in cardiovascular magnetic resonance imaging have revolutionized fibrosis assessment. Late gadolinium enhancement identifies focal replacement fibrosis, whereas native T1 mapping and extracellular volume quantification enable sensitive detection of diffuse interstitial fibrosis before overt ventricular dysfunction develops. Complementary echocardiographic techniques, circulating biomarkers, and emerging artificial intelligence–based imaging analyses further enhance early risk stratification. Although no pediatric-specific antifibrotic therapy currently exists, growing evidence suggests that modulation of the renin–angiotensin–aldosterone system, neprilysin inhibition, sodium–glucose cotransporter-2 inhibitors, mineralocorticoid receptor antagonists, and novel anti-transforming growth factor-β strategies may attenuate myocardial remodeling in selected patients. This review summarizes contemporary mechanisms underlying pediatric myocardial fibrosis, highlights advances in imaging biomarkers, discusses clinical implications across major pediatric cardiovascular diseases, and explores emerging antifibrotic therapies that may redefine future management.